The immune phenotype of tongue squamous cell carcinoma predicts early relapse and poor prognosis - Giuseppe Troiano (Cancer Medicine, 2020)
Abstract Background In patients with squamous cell carcinoma of the oral tongue (OTSCC), current tumor node metastasis staging system fails to identify at‐risk patients associated with early relapse and poor prognosis despite complete surgical resection. Given the importance of tumor‐infiltrating lymphocytes (TILs) in the development of cancers, here we investigated the prognostic significance of the immune phenotype in OTSCC. Methods Hematoxylin‐eosin stained sections of OTSCCs from 211 patients were evaluated. Cancers were classified as (a) immune‐inflamed when TILs were found next to tumor cell nests; (b) immune‐excluded when TILs were found in the stroma, outside the tumor; and (c) immune‐desert for tumors lacking lymphocyte infiltrate. The prognostic significance of these immune phenotypes classes was investigated. Data were further validated on an independent cohort from The Cancer Genome Atlas database. Results Immune‐desert phenotype was the least represented group of OTSCCs in our cohort (11.8%) and served as an independent prognostic factor. Patients with immune‐desert tumors exhibited worse disease‐specific survival (HR = 2.673; [CI: 95% 1.497‐4.773]; P = .001), overall survival (HR = 2.591; [CI: 95% 1.468‐4.572]; P = .001), and disease‐free survival (HR = 2.313; [CI: 95% 1.118‐4.786]; P = .024) at multivariate analysis. Conclusions We identified a specific subgroup of OTSCCs with poor prognosis. Tumor‐infiltrating lymphocytes density and localization could serve as an integrative parameter to the current staging system and inform the selection of most appropriate treatments. In particular, the tumor immune phenotype could improve the stratification of patients with more aggressive disease.